Targeted therapy of underlying conditions improves quality of life in patients with persistent atrial fibrillation: results of the RACE 3 study. Issue 4 (9th January 2019) - De With, Ruben R; Rienstra, Michiel; Smit, Marcelle D; Weijs, Bob; Zwartkruis, Victor W; Hobbelt, Anne H; Alings, Marco; Tijssen, Jan G P; Brügemann, Johan; Geelhoed, Bastiaan; Hillege, Hans L; Tukkie, Raymond; et al.
Abstract: Aims: Atrial fibrillation (AF) reduces quality of life (QoL). We aim to evaluate effects of targeted therapy of underlying conditions on QoL in patients with AF and heart failure (HF). Methods and results: The Routine versus Aggressive risk factor driven upstream rhythm Control for prevention of Early atrial fibrillation in heart failure (RACE 3) study randomized patients with early persistent AF and HF to targeted or conventional therapy. Both groups received guideline-driven treatment. The targeted group received four additional therapies: mineralocorticoid receptor antagonists; statins; angiotensin converting enzyme inhibitors and/or receptor blockers; and cardiac rehabilitation including physical activity, dietary restrictions, and counselling. Quality of life was analysed in 230 patients at baseline and 1 year with available Medical Outcomes Study Short-Form Health Survey (SF-36), University of Toronto AF Severity Scale (AFSS) questionnaires, and European Heart Rhythm Association (EHRA) class. Improvements in SF-36 subscales were larger in the targeted group for physical functioning (Δ12 ± 19 vs. Δ6 ± 22, P  = 0.007), physical role limitations (Δ32 ± 41 vs. Δ17 ± 45, P  = 0.018), and general health (Δ8 ± 16 vs. Δ0 ± 17, P  < 0.001). Dyspnoea at rest improved more (Δ−0.8 ± 1.3 vs. Δ−0.4 ± 1.2, P  = 0.018) and EHRA class was lower at 1-year follow-up in the targeted group. Patients with AF at 1 year, improvement in physical functioning (Δ9 ± 9 vs. Δ−3 ± 16, P  = 0.001), general health (Δ7 ± 16 vs. Δ−7 ± 19, P  = 0.004), and social functioning (Δ6 ± 23 vs. Δ−4 ± 16, P  = 0.041) were larger in the targeted group. Conclusion: A strategy aiming to treat underlying conditions improved QoL more compared with conventional therapy in patients with early persistent AF and HF. Its benefit was even observed in patients in AF at 1 year. Trial registration number: Clinicaltrials.gov NCT00877643.